A presença do léxico indígena nas toadas do Boi-Bumbá de Parintins - Silva, Dulcilândia Belém da (2015)
Parintins folk Festival is popular celebration that promotes a competition between two oxen: Caprichoso and Garantido. The event is annual party held in the brazilian city of Parintins, Amazonas state, during three days in late june. This place is well-knowm as Tupinambarana Island, in honor of the indigenous tribe inhabited in that place, which Highligts historical relations of indigenous presence in this area and strong influence on the constituion of cultural identify of people from Parintins. Among the 21 items that compose the Festival which are evoluated by a judging panel, the Boi-Bumbá tunes are mentioned, 11 items. From the end of the 80’s, its was observed, the letters of tunes, letters started to appear from the indegenous Tupi. In order to understand this innovation is that this study developed. The goal is to known the process by which indigenous words into the creative composition of the authors of the lyrics of tunes of Boi-bumbá. The research was conducted from 1986, when it was detected the start of the indigenous vocabulary, until 2013. The corpus consisted of 1.014 tunes, of which 466 had indigenous vocabulary, counting for them a total of 2.327 indigenous words. When not considered repetitions of the same word, this number decreased to 1.354. So, it appaears as they are selected by composers, to which lexical fields belong, what are the most commom, what are motivations of this change and its impact in the context of the community who constitute the population of Parintins. With this, intend to contribute to the promotion enhancement of indigenous culture, through the elaboration of a dictionary of words from indigenous languages and their occurrence in the context of the tunes Bumbás Caprichoso e Garantido, cultural identity of the inhabitants of Tupinambarana island. For this, occur as are selected, the frequency in which they occur as well as the motivations and implications of such inclusion in Parintins community. This is intended to contribute to the spread of knowledge and appreciation of indigenous languages and cultures, through the development of an indigenous topicalized dictionary words contained, whith 211 entries, in tunes letters of Bumbás Caprichoso and Garantido, pointing their meanings and their contexts. Key-Words: Indigenous lexicon, Parintins Festival, cultural identify.